Binuclear magnesium amidoborane complexes: Characterization of a trinuclear thermal decomposition product - Spielmann, Jan; Harder, Sjoerd (Dalton Transactions, 2011)
The bis-β-diketimine with a meta-phenylene bridge (META-H : DIPPN(H)CMeCHCMeN-C H -NCMeCHCMeN(H)DIPP; DIPP = 2,6-iPr-C H ) reacted with two equivalents of nBu Mg to give the bis-β-diketiminate complex META-(MgnBu) . The latter binuclear magnesium complex was converted to META-[MgNH(iPr)BH ] by reaction with H N(iPr)BH . The thermal decomposition of this binuclear iPr-substituted magnesium amidoborane complex has been investigated. In benzene it starts to eliminate H at 90 °C. Two decomposition products could be obtained by fractional crystallization of the residue. The first product is the trinuclear magnesium complex META-Mg [iPrNB(H)N(iPr) BH ] and the second product is (META-Mg) . These products have been formed by ligand exchange reactions of the expected complex META-Mg [iPrNB(H)N(iPr)BH ] and were characterized by single crystal X-ray diffraction. The central Mg ion in META-Mg [iPrNB(H)N(iPr)BH ] is not connected to the ligand system and its coordination geometry could be representative of that in a solid-state magnesium salt containing the RNB(H)N(R)BH ion. © The Royal Society of Chemistry 2011.